2011
DOI: 10.1167/iovs.10-6214
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lens-Induced Anisometropia on Accommodation and Vergence during Human Visual Development

Abstract: Accommodative and vergence gains of the typically developing visual system deteriorated marginally (accommodation more than vergence) with transiently induced anisometropia (up to ±4 D) and did not deteriorate significantly with induced aniseikonia of 11%. Some binocular cues remained with ±4 D of induced anisometropia and 11% induced aniseikonia, as indicated by the accommodative and vergence gains being higher than in monocular viewing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Phillips studied eighteen, 11-year-old myopic children who wore a monovision spectacle correction over a 30 month period. Although participant numbers are small and though it contained only myopes, this study tentatively suggests that anisometropes may habitually focus the less ametropic eye, generating chronic defocus in the more ametropic eye (also see Bharadwaj and Candy, 2011). Consistent with this observation, amblyopia is generally found in the more ametropic eye of both anisohyperopes and anisomyopes (Rutstein and Corliss, 2004).…”
Section: Cause and Effect: A Classic Chicken And Egg Storymentioning
confidence: 70%
See 1 more Smart Citation
“…Phillips studied eighteen, 11-year-old myopic children who wore a monovision spectacle correction over a 30 month period. Although participant numbers are small and though it contained only myopes, this study tentatively suggests that anisometropes may habitually focus the less ametropic eye, generating chronic defocus in the more ametropic eye (also see Bharadwaj and Candy, 2011). Consistent with this observation, amblyopia is generally found in the more ametropic eye of both anisohyperopes and anisomyopes (Rutstein and Corliss, 2004).…”
Section: Cause and Effect: A Classic Chicken And Egg Storymentioning
confidence: 70%
“…First, accommodation must remain yoked in the two eyes as unequal or uncoupled accommodation responses could theoretically bring both retinal images into focus. Most studies (Ball, 1952; Flitcroft et al, 1992; Koh and Charman, 1998; Bharadwaj and Candy, 2011; but see Horwood and Riddell, 2010) find that accommodation is consensual in the presence of anisometropia but small amounts of aniso-accommodation have been reported by Marran and Schor (1998, 1999), which may reflect the need for small amounts of aniso-accommodation with eccentric gaze (Charman, 2011). Second, for anisometropia to generate chronic defocus in one eye, anisometropes must habitually focus the other eye.…”
Section: Cause and Effect: A Classic Chicken And Egg Storymentioning
confidence: 99%
“…Banks et al . reported that altered retinal image size influences ocular dominance status during asymmetric convergence from the mid‐sagittal plane, however, Bharadwaj and Candy observed that lens induced aniseikonia up to 11% did not influence accommodation or vergence in adults. Since the dominant eye displayed a small but significantly greater accommodative response under binocular viewing conditions (with symmetrical vergence demands) irrespective of which eye received the monocular defocus, it is unlikely that the induced aniseikonia significantly influenced the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The response can be a purposeful suppression of one image while accommodating on the other; this might be a very difficult binocular task for children. In typically developing children (3.1 months to 12.1 years) induced aniseikonia (by placing a 11% afocal magnifier to the right eye) did not significantly influence the gain of accommodation and vergence ( Bharadwaj and Candy, 2011 ), but the effect of aniseikonia on visually impaired children is still unclear. Magnifier use was compared to enlarged print ( Huurneman et al, 2013 ), but in this static task there was no cue conflict between the two eyes because they used a large dome magnifier enabling children to look at the symbols binocularly and perception of the surroundings was not relevant.…”
Section: Discussionmentioning
confidence: 99%